Comparative Legal Analysis of Indonesian and South Korean Consumer Protection in Cosmetic Safety Regulations - Supardi, Reisha Rizkia Sabila; Hutabarat, Sylvana Murni Deborah (Rechtsidee, 2025)
General Background: The rapid growth of the cosmetics industry and new product innovations challenge businesses to remain competitive while meeting consumer expectations and legal standards. Specific Background: Given their direct application to the human body, cosmetic product safety is crucial, as non-compliance can pose health risks. Knowledge Gap: Despite existing regulations, hazardous cosmetic products still circulate. Understanding the production limits of business actors is essential to ensure consumer safety.Aims: This research uses normative legal analysis to compare cosmetic safety regulations in Indonesia and South Korea, focusing on consumer protection through comparative, statutory, and case approaches. Results: Both countries incorporate consumer protection principles in their cosmetic regulations. However, South Korea is more advanced with specific cosmetic laws. Novelty: The study presents a comparative analysis of cosmetic safety laws in Indonesia and South Korea, supported by international references. Implications: The findings offer insights into regulatory frameworks and suggest Indonesia adopt a more specific law, akin to South Korea’s Cosmetics Act, to improve consumer safety standards. Highlights: South Korea’s Cosmetics Act offers a more specific and advanced regulatory model. Unsafe cosmetics still circulate in Indonesia despite existing laws. Comparative legal analysis reveals the need for regulatory reform in Indonesia. Keywords: Comparative Law, Consumer Protection, Cosmetic, Regulation, Safety Standards